Khrushchev Report - Louis Ulrich (Sfera Politicii, 2013)
The Twentieth CPSU Congress was crucial for the evolution of the USSR, as well as for the other communist countries, by triggering the process of de-Stalinisation. To highlight this historical reality, the current article provides the context in which the Khrushchev Report was prepared, how it was presented at the Congress and the implications it has had on the international communist movement.